Efficient Synthesis of Natural Product Inspired Naphthoquinone-Fused Glycohybrids and Their In Silico Docking Studies - Khanna, Ashish; Tiwari, Ghanshyam; Mishra, Vinay Kumar; Singh, Kavita; Sagar, Ram (Synthesis, 2023)
Naphthoquinones, a diverse group of natural compounds with a 1,4-naphthoquinone core structure, have gained attention for their pharmacological properties. The anticancer activity of these compounds is attributed to their ability to accept electrons, leading to the generation of reactive oxygen species that cause DNA damage and cell death. In recent studies, hydroxy-1,4-naphthoquinone derivatives, including daunorubicin, have shown promising inhibitory effects against several human cancers, such as acute myeloid leukemia, chronic myelogenous leukemia, and Kaposi’s sarcoma. To further explore their potential as anticancer agents, this research article focuses on the design and synthesis of natural product inspired naphthoquinone-based glycohybrids. These glycohybrids are designed based on the structures of bioactive aryl glycosides and quinones, aiming to enhance their binding affinity and specificity towards cancer-related protein targets. The interactions between the synthesized glycohybrids and target proteins through computational docking simulations has been studied and better binding affinity was found.
Keywords: naphthoquinones; quinones; glycohybrids; glycosides; microwave irradiation; electrocyclization